Investigative baseline reference on the status of pork pH, shear force, colour, drip and cooking loss in RYR1 mutation free, commercial 3-way crosses in Malaysia - Fong, Michelle Wai Cheng; Ooi, Peck Toung; Sazili, Awis Qurni; Goh, Yong Meng (Universiti Putra Malaysia Press, 2018)
This paper attempts to provide findings of an investigative study on the baseline status of the pork quality in Malaysia. With consumer preferences changing towards the selection of good quality meat for consumption, there is a need to establish an investigative reference for the operators in the industry to gauge the performance of their animals and pork quality. This is also important to increase the competitiveness among producers to continuously improve the pork quality available to consumers. In this study, 30 commercial three-way crossed female pigs were randomly selected from government accredited abattoirs from east and west Malaysia and longisimus dorsi were collected for the determination of pH, drip loss, cooking loss, shear force and colour. All animals were screened for the RYR1 gene and the results were then compiled with statistical analysis to obtain an investigative baseline pork quality data in Malaysia. The average pork quality obtained from this study falls within the category of Red, Soft and Exudative (RSE), with an average ultimate pH of 5.83, drip loss more than 5% and L* values at 45.94. We have proposed an investigative baseline meat quality data for Malaysian pork from the average commercial pork quality data obtained. The proposed investigative pork quality baseline data in Malaysian is comparable in terms of studies done in other established countries and/or with international standards and falls within the RSE category of acceptable quality. It provides an investigative benchmark for researchers and end-producers to judge the quality of pork in an objective manner, both for consumption and for export purpose. Moreover, continuous selection against the RYR1 gene has successfully removed the gene from the sample size above, but constant random monitoring is still advisable if farms aim to ensure the elimination of this gene from their herd.